Candida parapsilosis Lumbar Spondylodiscitis as a Cause of Chronic Back Pain. Issue 6 (November 2018) - Khoo, Teresa; Psevdos, George; Wu, Judy
Abstract : Abstract: Vertebral bone infections caused by Candida species are uncommon, but their reported frequency is increasing. Candida parapsilosis, a commensal of human skin, is currently an emerging human pathogen, with increasing prevalence and medical significance. We report the case of a Caucasian man who presented with C. parapsilosis spondylodiscitis, who was having a persistent low back pain for 3 months before diagnosis. He had no history of immunosuppression, fever, or elevation of inflammatory markers. The diagnosis was made by fine needle aspiration and culture. A combined medical and surgical intervention was necessary to achieve the best outcome in our case. Abstract : Vertebral bone infections caused by Candida species are uncommon, but their reported frequency is increasing. Candida parapsilosis is currently an emerging human pathogen with increasing prevalence and medical significance. The authors report the case of a man who presented with C. parapsilosis spondylodiskitis, who had persistent low back pain for 3 months prior to diagnosis. He had no history of immunosuppression, fever, or elevation of inf lammatory markers. The diagnosis was made by fi ne needle aspiration and culture. A combined medical and surgical intervention was necessary.